Highly sensitive detection of dopamine, ascorbic and uric acid with a nanostructure of dianix yellow/multi-walled carbon nanotubes modified electrode. (15th October 2020) - Hatefi-Mehrjardi, Abdolhamid; Karimi, Mohammad Ali; Soleymanzadeh, Mahdiyeh; Barani, Azam
Graphical abstract: Highlights: Use of an electropolymerized film of dianix yellow along with MWCNT as a base. The above nanocomposite film show high electrocatalytic activity toward small biomolecules. Design of a novel modified electrode for high sensitive and selective detection of DA, AA, and UA. The method to be robust, inexpensive and fast for biological sample analysis. The fabricated sensor indicated the lowest detection limit with great repeatability in determination of DA, AA and UA. Abstract: A glassy carbon electrode has been modified with electrochemical polymerization of dianix yellow (PDY) along with multi-walled carbon nanotubes (MWCNTs) and utilized for the selective determination of dopamine (DA), ascorbic acid (AA) and uric acid (UA). AFM and SEM images compared the surface morphology and topography of bare and modified electrodes. The electrochemical activities of DA, AA and UA on the bare and modified electrodes were compared with cyclic, linear sweep, and differential pulse voltammetry (DPV). Large peak separation, good sensitivity and stability allow the PDY/MWCNTs modified electrode to analyzing DA individually and simultaneously in the presence of AA and UA. The DPV data showed DA, AA and UA peak currents are linear in the concentrations ranges of 0.7–2500 nM, 5–110 µM and 0.100–7.500 µM. respectively. Also, the respected detection limits obtained with this method were 0.7, 9.9 and 8.9 nM. The practical analytical application of this modified electrode was demonstrated by DA determination in human blood serum samples.